2013
DOI: 10.4103/2321-0656.115304
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and readability assessment of patient information leaflets for diabetic foot ulcers

Abstract: Context: Patient counseling is the mainstay for prevention and management of diabetic foot ulcer. Hence, patient information leaflet (PIL) can act as an educational material for imparting patient education regarding diabetic foot care for better patient outcome.Aim: The objective of this study was to develop and to assess the readability of PIL for diabetic foot ulcer.Materials and Methods: Various online resources such as Patient UK and Micromedex data base were used to prepare PILs on diabetic foot ulcer. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The PIL developed in this study scored > 25 in both English and Kannada versions and were similar to an English PIL prepared by the authors in a previous study (16). …”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The PIL developed in this study scored > 25 in both English and Kannada versions and were similar to an English PIL prepared by the authors in a previous study (16). …”
Section: Discussionsupporting
confidence: 76%
“…The FK-GL of the PIL gave a score of 6.1, which approximately equates to a reading age of between 11 and 12 years old. A previous study on readability of PIL for DFU reported a FK-GL score of 7.1 (16). Gunning-Fog index estimates the years of formal education needed to understand written text on a first reading.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, the design and layout of the PILs was assessed using BALD criteria and the scores were 25 for English and Malayalam, and 26 for Kannada PILs. The scoring was fair with respect to the scoring done in PIL's made in similar studies conducted by Adepu R et al, Roy RT et al and Mateti UV et al 5,6,8 The BALD score of the PIL in the study by Adepu R et al was 22, Roy RT et al was 27 and Mateti UV et al was 28 (English) and 26 (Kannada). 5,6,8 Our study results revealed that the occurrence of ACS was more predominant in male population than female population between the two groups.…”
Section: Discussionmentioning
confidence: 57%